The impact of psoriasis on work‐related problems: a multicenter cross‐sectional survey. (21st August 2013) - Ayala, F.; Sampogna, F.; Romano, G.V.; Merolla, R.; Guida, G.; Gualberti, G.; Paparatti, U.d.L.; Amerio, P.; Balato, N.; Potenza, C.; The Daniele Study Group
Abstract Background Psoriasis can have cumulative physical and psychosocial effects preventing sufferers from achieving their full‐life potential. Few studies have addressed the impact of psoriasis on work‐related characteristics. Objective To evaluate the impact of psoriasis on education prospects and work limitations in patients with moderate‐to‐severe psoriasis. Methods This study was conducted in 29 dermatology centres across Italy. Information was collected by questionnaire during office visits. Results A total of 787 patients (64% male, aged 50 years) completed the questionnaire. At the time of the survey, mean Psoriasis Area and Severity Index (PASI) score and disease duration were 10 and 19 years respectively. Current smokers had higher PASI scores compared to non‐smokers (10.8 vs. 9.4, P = 0.02). Plaque psoriasis was the most frequently described (91.2%). Fifty‐five percent of patients had limited expectations of career progression. Similarly, in 42% of cases, psoriasis reduced the prospects of improvement in employment status and 35% of patients reported having reduced earning potential. Approximately 60% of patients reported that psoriasis localized to their hands or feet caused work limitations, whilst in about 25%, it caused them to quit their job. Approximately 37% of patients reported having lost between 3–10 work days in the past 3 months due to clinical assessment or treatment. Logistic regression revealed that gender, low standard of education, number of localizations, shame, anger and self‐esteem were predictors significantly associated with limitations in work. Conclusions Moderate‐to‐severe psoriasis has a profound negative impact on the employment capacity of patients in Italy. Psoriasis also contributes to days lost from work, affects job opportunity, career prospects and revenue potential.